Pharmacovigilance and its role in the protection of medicine consumer - Boulassel, Mohamed; Belabed, Sami (Journal of Human Sciences, 2021)
Medicines are necessary and elementary products for health preservation of man. However, some medicines are dangerous and the least mistake in their production may had to disastrous inconvenient. Its harmfulness increases because some secondary effects appear after a long time that’s why some international authorities, even Algerian establish some laws and legislations for controlling, organizing and commercializing the product.  Hence, the Algerian legislator, has created an organization for medicine alert by the law 11-98 charging the national medicine agency to coordinate the work with other active organizations in the field, the national center for medicines declared: 192-98 where our problematic is concerned around the increasing of this organization efficiency? The first axes of this concern would be on the origin of the medicines products where as the second axes will deal with the role before and after their inscriptions.